Education: a dialogic between developing individuals or train citizens - Callet-Venezia, Ingrid (Formazione & insegnamento, 2020)
If already Jean-Jacques Rousseau (1712-1778) in the eighteenth century won-dered whether the role of education was to develop individuals or train cit-izens, the topic remains present nowadays in educational institutions. This article describes, reminding Rousseau's thoughts, how Italian and French educators operate in childcare centers by discussing the analyses of the interviews conducted in the sample of eight childcare centers in two countries: France and Italy. The results compare how the educators in the two contexts examined are compared to the tension already highlighted by Rousseau between individ-uality and society.